(3GdfLhe GdRhGgQ aj eYQaI GdChGNQs - (3GHf GddHhOj , CMeO Hf Ndjd Hf CMeO, CHh GdYHGS,J (B896 (3g` s ((3efRd GdeUfa HOeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdBNQ HYO fgGjI , GdChd HdG HOGjI Gdehab dWQjb GdgOGjI CeG HYO , aEf GdYdeGA bd Gf JQchG efgLkG eG Sdchg s
(3BNQgG (B:s
(3ajfhQ hLgc cf dPfHi ZGaQkG aYdjc ai ZaQGfg CJhcd BNQ GdfLhe GdRhGgQ ai eYQaI GdChGNQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B121 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B215s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs